Downstream testing after an halted coronary CT angiography due to high coronary artery calcium score. (25th November 2020) - Gama, F; Rocha, B; Freitas, P; Ferreira, A; Abecasis, J; Guerreiro, S; Saraiva, C; Santos, A.C; Andrade, M.J; Ventosa, A; Almeida, M; Pintao, S; et al.
Abstract: Background and aim: In many centers, coronary artery calcium score (CACS) is performed immediately before coronary CT angiography (CCTA) in order to exclude heavy calcification that could hamper test performance. When high CACS values are found, CCTA is usually aborted and other tests suggested. However, there are no recommendations on which test to pursue, and little data on their diagnostic yield in this setting. The aim of this study was to assess the type and results of downstream testing among patients whose CCTA study was halted due to high CACS. Methods: Single-centre retrospective study of consecutive patients undergoing CCTA for suspected obstructive coronary artery disease (CAD). A CACS threshold of >400 was generally used to cancel CCTA. Downstream testing and its results were assessed using electronic medical records. A group of consecutive patients with CACS <400 who underwent CCTA was used for comparison. Results: Of the 795 patients who performed CCTA for suspected CAD, 86 (10.8%), had their test halted due to high CACS (57 men, mean age 71±11 years). In this subgroup, the median pre-test probability for CAD was 27% (interquartile range 25) and the median CACS was 983 (interquartile range 930). Compared to patients who underwent CCTA, those who saw their tests cancelled were older, more frequently male, and had higher prevalence of cardiovascular risk factors and higher pre-test probability for CAD. Patient's downstream testing is illustrated in Figure. From the 86 patients enrolled, 12 are currently waiting for downstream tests and were excluded from further analysis. Overall, 35 patients ended up performing invasive coronary angiography (ICA, 47.3%) of whom 19 (54.3%) had significant CAD. Among those who underwent non-invasive testing (N=19, 25.7%), 10 (52.6%) had significant ischemia and 4 (21%) underwent additional testing with ICA. In 24 patients (32.4%), no downstream testing was pursued. Finally, 17 (22.3%) patients underwent coronary revascularization, either percutaneous (N=10, 13.5%) or surgical (N=7, 10.8%). Conclusion: Invasive coronary angiography is the most frequently used downstream test when CCTA is halted due to high CACS values, and shows significant CAD in roughly half of the cases. Considering the high prevalence of significant CAD, direct referral for ICA (with the possibility of invasive functional testing) seems a reasonable approach. Funding Acknowledgement: Type of funding source: None